Academic reform and sustainability of Islamic higher education in Indonesia. (March 2022) - Suyadi,; Nuryana, Zalik; Sutrisno,; Baidi,
Abstract: This research aimed to investigate the academic reform agenda in State Islamic University Sunan Kalijaga Indonesia. Examining this reform agenda is interesting to do because this academic reform has become an exemplary agenda which is followed by other Islamic higher education institutions in Indonesia. State Islamic University Sunan Kalijaga is the oldest Islamic higher education institution in Indonesia. Its existence is becoming a barometer for the survivability of other Islamic higher education institutions. The stagnation or progress of State Islamic University Sunan Kalijaga may become the indicator of the stagnation or progress of other Islamic higher education institutions. Therefore, the academic reform under investigation has had a significant and massive impact on the sustainability of other Islamic universities in Indonesia. This research employed a qualitative type of phenomenology involving 34 informants. These informants were the former dean at the university who served between 2007 and 2011, the head of departments, lecturers, and students. The data were collected by participant observation, indepth interview, and policy document. The results suggested that there were four major agendas of academic reform consisting of study program internationalization, new program opening, the integration of postgraduate management into the faculty and the opening of teacher certification program. These major reforms became the foundation and reference for other Islamic universities as they opened the opportunity for internationalization of Islamic higher education institutions in Indonesia. Highlights: The academic reform has had a significant and massive impact. Reform is a process of restructuring which be a quick change needed for improvement. Academic reform has opened the opportunity for internationalization of Islamic higher education institutions Academic reform ensures the sustainability of Islamic higher education.